From integrated to expedient: an adaptive framework for river basin management in developing countries - Lankford, B.A.; Merrey, Douglas J.; Cour, J.; Hepworth, N. (International Water Management Institute, 2007)
The authors reflect on the theory and process of creating effective strategies for adaptive river basin management. We formulate our framework from observations of responses to environmental and hydrological change in the Great Ruaha River in Tanzania. We find that problems occur in the pursuit of 'integrated water resources management' (IWRM) that can be attended to by applying a focused expedient approach in three states of the water availability regime: 'critical water', 'medial water' and 'bulk water'. In particular, less reliance on broad generic 'principles' and greater reference to solutions being drawn up by local resource users in relation to identified conflicts helps guide adaptive problem solving.